Caesarean sections and the prevalence of preterm and early-term births in Brazil: secondary analyses of national birth registration - Barros, F; Rabello Neto, D; Villar, J; Kennedy, S; Silveira, M; Diaz-Rossello, J; Victora, C (BMJ Publishing Group, 2018)
Objectives To investigate whether the high rates of caesarean sections (CSs) in Brazil have impacted on the prevalence of preterm and early-term births. Design Individual-level, cross-sectional analyses of a national database. Setting All hospital births occurring in the country in 2015. Participants 2 903 716 hospital-delivered singletons in 3157 municipalities, representing >96% of the country’s births. Primary and secondary outcome measures CS rates and gestational age distribution (<37, 37–38, 39–41 and 42 or more weeks’ gestation). Outcomes were analysed according to maternal education, measured in years of schooling and municipal CS rates. Analyses were also adjusted for maternal age, marital status and parity. Results Prevalence of CS was 55.5%, preterm prevalence (<37 weeks’ gestation) was 10.1% and early-term births (37–38 weeks of gestation) represented 29.8% of all births, ranging from 24.9% among women with <4 years of schooling to 39.8% among those with >12 years of education. The adjusted prevalence ratios of preterm and early-term birth were, respectively, 1.215 (1.174–1.257) and 1.643 (1.616–1.671) higher in municipalities with≥80% CS compared with those <30%. Conclusions Brazil faces three inter-related epidemics: a CS epidemic; an epidemic of early-term births, associated with the high CS rates; and an epidemic of preterm birth, also associated with CS but mostly linked to povertyrelated risk factors. The high rates of preterm and earlyterm births produce an excess of newborns at higher risk of short-term morbidity and mortality, as well as long-term developmental problems. Compared with high-income countries, there is an annual excess of 354 000 preterm and early-term births in Brazil.